PENINGKATAN KEMAMPUAN MENULIS PUISI MELALUI TEKNIK MIND MAP SISWA KELAS VIIA SMP NEGERI 1 PARIGI KABUPATEN PARIGI MOUTONG - Mustapa, Nortje (BAHASANTODEA, 2015)
Abstract The problem in this study were: 1) How was the application of mind mapping technique in teaching poetry writing skill of VIIa grade students at SMP Negeri 1 Parigi?, And 2) Did the use of mind mapping techniques can enhance the creativity of writing poetry as an expression of feeling of VIIa grade students at SMP Negeri 1 Parigi ? It was a classroom action research that consisting of 2 cycles. This research was conducted at SMP Negeri 1 Parigi, class VIIa with 32 students. In this study, the data collection techniques used observation, questionnaire and achievement test and the data analysis was descriptive and qualitative analysis. The results of the research and the analysis could be obtaine as follows: Increasing the ability of the students in write poetry in the first cycle reached an average of 64.16 increased to 87.28 in the second cycle. The conclusions drawn in this study was learning by applying the mind mapping technique Â improved the ability to write poetry of VIIa grade students at SMP Negeri 1 Parigi. Keywords: Mind Map Technique, Writing Poetry.